Estado de coisas inconstitucional: a precária capacidade institucional do Estado brasileiro em efetivar o direito fundamental à educação - Franca, Mariana Wanderley Cabral Monteiro da (2018)
This dissertation studies the institutional fragility of the Brazilian public power in effecting the fundamental right to education, characterizing this situation as unconstitutional behavior. The focus of the work is the national basic education, specifically analyzing the failures that compromise the educational system. It is evident the inertia of administrative and political institutions in solving the serious problems that mainly affect the teaching, at the fundamental and middle levels, damaging millions of young Brazilians. The work seeks to evaluate the best way to unlock the blockades that impede the full guarantee of the right to education and, therefore, of socio development. The work deals with the socio development as the fundamental objective of the Republic. It analyses, in general, fundamental rights in order to preserve the dignity of the human person. In this respect, it deals with the unconstitutional state of affairs, making a comparative study with some countries in Latin America. Then, it discusses the debate involving judicial activism, confronting it with the principle of separation of powers and the problem of the democratic legitimacy of the judiciary. Finally, it discusses the poor quality of education in Brazil. It also analyzes the mission of the judiciary through a dialogic activism, as a way to overcome the institutional obstacles that block the execution of this right, in a satisfactory way. The method of approach used was the dialectical, presenting a thesis with true pretension, putting it in conflict with an antithesis. The methods of procedure applied were the comparative and the functionalist. On the basis of the analysis of the institute of the unconstitutional state of affairs in other countries, it was possible to verify the purpose of its declaration in the effectiveness of fundamental rights. The research technique used was indirect documentation, through documentary and bibliographic research. Regarding the classification of the research, it is characterized as exploratory and qualitative.